2011
DOI: 10.1159/000324994
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of SU5416, a Selective Vascular Endothelial Growth Factor Receptor Tyrosine Kinase Inhibitor, on Experimental Corneal Neovascularization

Abstract: Purpose: Treatment of neovascularization in ocular diseases with vascular endothelial growth factor (VEGF) inhibition shows promising results. SU5416 is a low-molecular-weight tyrosine kinase inhibitor. It selectively inhibits the membrane-bound tyrosine kinase activity of VEGF-2 receptor (Flk-1/KDR) and blocks the intracellular signaling process. The aim of this study was to evaluate the effect of SU5416 on corneal neovascularization. Methods: Corneas were cauterized with silver nitrate/potassium nitrate stic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…Our findings align with previous studies that show that blocking the activity of Vegf-A with either Vegf-A receptor inhibitors or Vegf neutralizing antibodies suppresses neovascularization following corneal cautery [37,46,47]. In the present study we further demonstrated that Nox2 may play a role in Vegf mediated angiogenic responses following corneal cautery as we found reductions in neovascularization as well as gene and protein expression of Vegf-A and Flt1.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings align with previous studies that show that blocking the activity of Vegf-A with either Vegf-A receptor inhibitors or Vegf neutralizing antibodies suppresses neovascularization following corneal cautery [37,46,47]. In the present study we further demonstrated that Nox2 may play a role in Vegf mediated angiogenic responses following corneal cautery as we found reductions in neovascularization as well as gene and protein expression of Vegf-A and Flt1.…”
Section: Discussionsupporting
confidence: 93%
“…4 E ). Further, the VEGFR2 tyrosine kinase inhibitor, SU‐5416 (29–31) (Supplemental Fig. 4 D ), decreased the VEGF‐A‐mediated endoglin and VEGFR2 interaction (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…For example, treatment with SU5416, a selective inhibitor of VEGFR2 tyrosine kinase, had an inhibitory effect on alkali burn-induced corneal neovascularization in mice. 20 Regorafenib, an inhibitor of multiple tyrosine kinases including VEGFRs, inhibited corneal neovascularization in a similar animal model. 21 Treatment with oral small-molecule inhibitors of VEGFR reduced suture-induced hemangiogenesis in the cornea and enhanced the survival of allogenic corneal transplants in rats.…”
Section: Resultsmentioning
confidence: 99%